“It Was Like a Tsunami”: Challenges for Refugee Third-Sector Organizations at a Time of Repressive Asylum Policies - Degnen, Cathrine; Pasquetti, Silvia; Barnes, Hannah; Marchetti, Chiara; Rossi, Michele (Refuge, 2025)
Based on an innovative method of knowledge exchange with two third-sector organizations working with asylum migrants in Newcastle, UK, and Parma, Italy, we examine how each has reoriented what they consider as sanctuary-building work in response to repressive state asylum policies. This includes focusing on language and communication due to increasingly troubling anti-migration discourses that make the once unspeakable now speakable in both countries. Second, in response to different local government politics, they have sought different relationships with local institutions: autonomy in Parma and collaboration in Newcastle. The conclusion discusses how autonomous third-sector initiatives have more potential to build long-term sanctuary than those pursued through institutional collaboration.